Distribution of Interplanetary Dust Detected by the Juno Spacecraft and Its Contribution to the Zodiacal Light. Issue 3 (9th March 2021) - Jorgensen, J. L.; Benn, M.; Connerney, J. E. P.; Denver, T.; Jorgensen, P. S.; Andersen, A. C.; Bolton, S. J.
Abstract: The Solar System is home to a cloud of dust that orbits the Sun and makes its presence known by virtue of scattered light (Zodiacal Light) that can be seen after dusk and before dawn. Within this cloud are bands of dust orbiting near the ecliptic plane, evidenced by an excess of scattered light at discrete ecliptic latitudes. Dedicated dust detectors borne by spacecraft in transit of the solar system have detected few such particles of the appropriate size owing to limited detector aperture and sparsity of the population. Thus, the distribution, origin, and orbital evolution of the dust in these bands remains a mystery. A star camera aboard the Juno spacecraft traveling from Earth to Jupiter recorded interplanetary dust impacts on the spacecraft in numbers sufficient to characterize the spatial distribution of such particles for the first time. The observed distribution is consistent with a primary source of dust particles sharing the Mars orbit plane between Earth and the 4:1 resonance with Jupiter. We propose that the primary distribution is scattered by orbital resonances with Jupiter via the Kozai‐Lidov (KL) effect into a secondary population at higher inclination to the ecliptic. The measured dust distribution, occupying a volume uniquely determined by the orbital elements of Mars and KL scattering, accounts for the observed variation of the Zodiacal Light with ecliptic latitude. Our results provide a compelling alternative to the prevailing theory of the origin and evolution of interplanetary dust observed at low ecliptic latitudes. Plain Language Summary: The Zodiacal light is sunlight reflected by dust in the inner solar system. Variations in the Zodiacal light with ecliptic latitude reveal discrete bands of dust orbiting near the ecliptic plane. The Juno spacecraft, in transit from earth to Jupiter, recorded a sufficient number of impacts with this dust to characterize their distribution in space for the first time. The radial distribution of the dust suggests a primary source of dust with the orbital elements (inclination and eccentricity) of Mars, scattered into a secondary population at higher inclination to the ecliptic. The resulting population accounts for the observed variation of Zodiacal light with ecliptic latitude. Key Points: The Juno spacecraft, in transit from Earth to Jupiter, recorded the impact of interplanetary dust particles on its solar arrays in large numbers The distribution of dust near the ecliptic reveals the influence of mean motion resonances with Jupiter, providing clues to its origins The modeled dust distribution accounts for the variation in Zodiacal light with ecliptic latitude, scattered by the Zodiacal dust bands